Fifty years of library and information science education in Iceland - Jóhanna Gunnlaugsdóttir 1949- (2006)
Birtist í: E-Publications: Education for Library and Information Services: A Festschrift to Celebrate Thirty Years of Library Education at Charles Sturt University. Sjá: http://bcpwww.csu.edu.au/faculty/educat/sis/CIS/epubs/LISEducpapers.htm Instruction in library and information science (LIS) at the University of Iceland began in 1956 making the year 2006 the 50th anniversary. A new chapter in the history of the LIS Department began when a formal Master of Library and Information Science (MLIS) program was launched in 2004 under the leadership of Prof. Anne Clyde. Dr Clyde came to the department 15 years ago. She brought with her from Australia new disciplines and a new outlook regarding the utility of the Internet as ‘a library without walls’. She was instrumental in designing the master’s program. Methods in LIS have changed drastically in conjunction with rapid developments in information technology. These changes are reflected in the courses being offered. More emphasis is now placed on ties with the outside world, the profession and with industry. The objective is to meet demands for knowledge and skills in industry without reducing academic requirements. By the end of 2005 a total of 448 students had graduated in LIS from the University of Iceland with a BA degree. Two students have so far finished their MLIS degree.